National Guidelines for Human Rights Education in legal teaching: normative, epistemic and formative issues: Diretrizes Nacionais para a Educação em Direitos Humanos no ensino jurídico: questões normativas, epistêmicas e formativas (Revista Cocar, 2023)
The present investigation scales some specificities and nuances that systematize legal education, in dialogue with human rights education, aiming to understand to what extent human formation and the ethical-formative principles of the National Guidelines for Human Rights Education have contributed to legal education. From a methodological point of view, this study is based on a bibliographical research, with a qualitative approach. We intend to offer some reflections on the contributions and interfaces between legal education in interface with the ethical-political-training principles suggested by the National Guidelines for Human Rights Education. Some theoretical and epistemic contributions are offered to the process of understanding the National Guidelines for Human Rights Education and its implementation in legal education, especially in relation to the criticism of the neoliberal logic that underlies legal education.Keywords: Human rights education; Human development; Higher education. ResumoA presente investigação dimensiona algumas especificidades e nuances que sistematizam a educação jurídica, em diálogo com a educação em direitos humanos, tendo como objetivo compreender em que medida a formação humana e os princípios ético-formativos das Diretrizes Nacionais para Educação em Direitos Humanos têm contribuído para o ensino jurídico. Do ponto de vista metodológico, este estudo é instrumentalizado a partir de uma pesquisa bibliográfica, de abordagem qualitativa. Pretendemos oferecer algumas reflexões acerca das contribuições e interfaces entre a formação jurídica em interface com os princípios ético-políticos-formativos sugeridos pelas Diretrizes Nacionais para Educação em Direitos Humanos. São oferecidas algumas contribuições teóricas e epistêmicas ao processo de compreensão das Diretrizes Nacionais para Educação em Direitos Humanos e sua implementação no ensino jurídico, sobretudo em relação à crítica à lógica neoliberal que fundamenta a educação jurídica.Palavras-chave: Educação em direitos humanos; Formação humana; Ensino superior.